Effect of solvent surface tension on optical limiting properties of graphene dispersions. (12th February 2015) - Sun, Xuehui; Yan, Lihe; Chen, Tao; Yu, Yang; Matsuo, Shigeki
Abstract: The optical limiting (OL) properties and the mechanisms of graphene dispersions in alcohol aqueous solutions with different concentrations were investigated using a nanosecond pulse laser. With increasing the incident laser influence, optical transmittance of graphene dispersions decreased and the nonlinear scattering (NLS) light intensity increased synchronously, indicating that the NLS effect was mainly responsible for the OL process of graphene dispersions. By changing the alcohol concentration in the solvent and analyzing the relations between the solvent surface tensions and the OL properties of different dispersions, we demonstrated that solvent surface tension played a significant role in the OL performance of graphene dispersions, and a lower surface tension would induce a stronger NLS effect and a lower OL threshold.